2019
DOI: 10.3390/ani9100841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pegbovigrastim on Hematological Profile of Simmental Dairy Cows during the Transition Period

Abstract: Simple SummaryDuring the transition period (TP), the innate and adaptive immune system of dairy cows is impaired, contributing to an increase in susceptibility to infectious disease. Pegbovigrastim is a recombinant form of the granulocyte colony-stimulating factor, that stimulates differentiation of hemopoietic stem cells to granulocyte and shortens maturation time within the bone marrow and their release in circulation. For the first time, this study investigated the effect of pegbovigrastim on the hematologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…MPO synthesis is mainly limited to myeloid cells in the bone marrow. The influence of pegbovigrastim on MPO expression, an enzyme stored in azurophilic granules of granulocytes, agreed with increased bone marrow production induced by treatment in the study of Trimboli et al [40]. In this case, our results were opposite those reported by Heiser et al [15] for the same gene, i.e., pegbovigrastim did not upregulate MPO.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…MPO synthesis is mainly limited to myeloid cells in the bone marrow. The influence of pegbovigrastim on MPO expression, an enzyme stored in azurophilic granules of granulocytes, agreed with increased bone marrow production induced by treatment in the study of Trimboli et al [40]. In this case, our results were opposite those reported by Heiser et al [15] for the same gene, i.e., pegbovigrastim did not upregulate MPO.…”
Section: Discussionsupporting
confidence: 90%
“…In this respect, Rado et al [44] suggested that lactoferrin (involved in several physiological and protective functions, including regulation of iron absorption in the bowel and mainly antimicrobial activities [46]) is synthetized in developing neutrophils during the maturation process and present in secondary granules of PMNs. Thus, the latter could imply that pegbovigrastim was also able to induce neutrophils' maturation (supported also by the greater levels of MPO and LCN2), besides the effect of stimulating the formation of granulocyte colonies from bone marrow-derived precursors [40].…”
Section: Discussionmentioning
confidence: 97%
“…Pegfilgrastim is most widely used synthetic immunostimulant of G-CSF production [ 103 ]. In agriculture, a bovine G-CSF or its inducer pegbovigrastim are administered to cattle prior to parturition to boost the immune system and decrease the incidence of mastitis [ 104 , 105 , 106 ].…”
Section: Alternative Strategies To Combat Antibiotic Resistancementioning
confidence: 99%
“…Several studies have shown that in cattle, the administration of Pegbovigrastim provides a well-tolerated approach to overcoming periparturient immune suppression, making it possible to restore normal neutrophil function [ 62 , 75 ]. The administration of Pegbovigrastim induces a state of neutrophilia, characterized by a ‘left-shift’ towards progenitor cells with a release of mature neutrophils and band cells from storage pools in bone marrow [ 76 , 77 ]. Pegbovigrastim is found to induce a slight decrease of red cell count and hematocrit in cows treated 7 and 21 days after calving [ 62 , 77 ].…”
Section: Another Drug: Pegbovigrastimmentioning
confidence: 99%
“…The administration of Pegbovigrastim induces a state of neutrophilia, characterized by a ‘left-shift’ towards progenitor cells with a release of mature neutrophils and band cells from storage pools in bone marrow [ 76 , 77 ]. Pegbovigrastim is found to induce a slight decrease of red cell count and hematocrit in cows treated 7 and 21 days after calving [ 62 , 77 ]. The finding of normocytic, hypochromic anemia in 50% (8/16) and 19% (3/16) of the Pegbovigrastim treated and control cows, respectively, could indicate an increased anemic effect after treatment with this immune stimulant [ 77 ].…”
Section: Another Drug: Pegbovigrastimmentioning
confidence: 99%